Pronoun processing in Broca's aphasia: Discourse-syntax effects in ambiguous anaphora resolution - Peristeri, E.; Tsimpli, I. M. (Aphasiology, 2013)
Background: The interpretation of ambiguous subject pronouns in a null subject language, like Greek, requires that one possesses grammatical knowledge of the two subject pronominal forms, i.e., null and overt, and that discourse constraints regulating the distribution of the two pronouns in context are respected. Aims: We investigated whether the topic-shift feature encoded in overt subject pronouns would exert similar interpretive effects in a group of seven participants with Broca's aphasia and a group of language-unimpaired adults during online processing of null and overt subject pronouns in referentially ambiguous contexts. Method & Procedures: An offline picture-sentence matching task was initially administered to investigate whether the participants with Broca's aphasia had access to the gender and number features of clitic pronouns. An online self-paced listening picture-verification task was subsequently administered to examine how the aphasic individuals resolve pronoun ambiguities in contexts with either null or overt subject pronouns and how their performance compares to that of language-unimpaired adults. Outcomes & Results: Results demonstrate that the Broca group, along with controls, had intact access to the morphosyntactic features of clitic pronouns. However, the aphasic individuals showed decreased preference for non-salient antecedents in object position during the online resolution of ambiguous overt subject pronouns and preferred to pick the subject antecedent instead. Conclusions: Broca's aphasic participants' parsing decisions in the online task reflect their difficulty with establishing topic-shifted interpretations of the ambiguous overt subject pronouns. The presence of a local topic-shift effect in the immediate temporal vicinity of the overt pronoun suggests that sensitivity to the marked informational status of overt pronouns is preserved in the aphasic individuals, yet, it is blocked under conditions of global sentential processing.